PROFIL KEMAMPUAN SISWA SMP DALAM MENYELESAIKAN SOAL GEOMETRI TIDAK RUTIN DENGAN MENGGUNAKAN MODEL POLYA - Santoso Yohanes, Rudi (Widya Warta, 2018)
Non-routine problem is very important to learn. Besides to improve mathematics achievement,  non-routine problem is a means to train students to use their logic, think critically, become creative, and develop their intuition. This research was a qualitative descriptive-exploratory; it aimed to determine the profile of abilities of the junior high school students in solving non routine geometry problems using Polya model. The subjects were 10 junior high school students following Olympics coaching which were coached by the researcher. The olympics coaching model used was that the students were asked to solve the given problems using Polya’s 4-step problem solving, namely understanding the problem, devising a plan, carrying out the plan, and looking back. Students were also given the opportunity to try to resolve the problem by using their own ways. Afterward, they followed the discussion. The teacher acted as a facilitator, motivator, and consultant, who monitored whether the students’ ways worked or not. The data consisted of the students’ solving of the non-routine geometry problems; the data were analyzed qualitatively to determine if the students had used Polya’s 4-step problem solving model, and to know if there were the students’ weaknesses which were needed to be improved. The results showed that the second step of Polya model, namely devising a plan, was considered the most difficult by most students. The students still had difficulty in finding the initial idea to solve non-routine problem.